Development of A Mathematical Equation to Predict Serum Total Bilirubin Level Correlating Body Mass Index (BMI) - Bandara, WGNM; Gunasekara, ADBR; Vidyathilaka, MG; Dias, P; Priyadarshani, AMB (International Journal of Human and Health Sciences (IJHHS), 2026)
A descriptive, cross-sectional study was conducted to derive a mathematical equation to predict the serum total bilirubin level in terms of body mass index (BMI). We recruited 109 apparently healthy women within 20-28 years. The height and weight were measured using standard protocol to calculate the BMI. The serum total bilirubin level was measured by bilirubin total kit (VOX method) with Mindray BS-240 fully automated biochemistry analyzer. Percentage distribution of individuals according to the BMI categories was 25.7, 28.4, 19.3 and 26.6% for underweight, normal, overweight and obese, respectively with the median BMI of 21.3 kg/m², (interquartile range (IQR) of 6.9 kg/m²). The median serum total bilirubin level was 0.69 mg/dL with the IQR of 0.21 mg/dL. The underweight group had the maximum serum total bilirubin median value (1.12 mg/dL) whereas the obese group had the minimum median value (0.41 mg/dL). The serum total bilirubin level was negatively correlated with BMI (r=-0.686, p<0.001). Based on the findings, the mathematical model derived was “serum total bilirubin level (mg/dL)=0.1+13.051/BMI”. This shows when there is an increase in 1/BMI by one unit, serum total bilirubin level is predicted to be increased by 13.051 units. A statistically significant moderately strong negative relationship was observed between serum total bilirubin levels and BMI in the study population. International Journal of Human and Health Sciences Vol. 10 No. 02 Apr’26 Page: 103-108